Survival Status and Predictors of Mortality among Newborns Admitted with Neonatal Sepsis at Public Hospitals in Ethiopia - Samuel Dessu; Aklilu Habte; Tamirat Melis; Mesfin Gebremedhin (International Journal of Pediatrics)
Background. One-fourth of neonatal death is due to neonatal sepsis and nearly 98% of these deaths are occurring at low- and middle-income countries. In Ethiopia, forty percent of under-five mortality occurs during the neonatal period, of which neonatal sepsis accounts for 30-35% of neonatal deaths next to prematurity and its complications. On the other side, among the survived neonates with neonatal sepsis, there exist as vulnerable to short and long-term neurological and developmental morbidity impacting the overall productivity of the child as adult. Methods. A longitudinal prospective cohort study was conducted among selected 289 neonates with neonatal sepsis who were admitted in the neonatal intensive care unit at public hospitals in Ethiopia from 1st March 2018 to 31st December 2019. Data were entered into Epi data version 3.02 and exported to SPSS V 25 for analysis. The Kaplan-Meier survival curve together with log-rank test was used to estimate the survival time of the neonates. Variables which had p value < 0.05 in multivariable analysis using the cox proportional hazard model were declared as statistically significant predictors of mortality. Results. The study was conducted with a total of 289 neonates admitted with neonatal sepsis. The cumulative proportion of surviving at the end of the fourth day was 99.5%, and it was 98.2% at the end of the fifth day. In addition, it was 96.6%, 93.5%, and 91.1% at the end of the sixth, seventh, and eighth day, respectively. The incidence of mortality was 8.65 per 100 neonates admitted with neonatal sepsis. Having a history of intrapartum fever (AHR: 14.5; 95% CI: 4.25, 49.5), history of chorioamnionitis (AHR: 5.7; 95% CI: 2.29, 13.98), induced labor (AHR: 7; 95% CI: 2.32, 21.08), and not initiating exclusive breastfeeding within one hour (AHR: 3.4; 95% CI: 1.34, 12.63) were the independent predictors of mortality. Conclusion. The survival status of neonates among neonates admitted with neonatal sepsis was high at the early admission days and high cumulative proportion of death as the admission period increased. The risk of mortality was high among the neonates with early onset of neonatal sepsis as compared with late onset of neonatal sepsis and history of intrapartum fever, history of diagnosed chorioamnionitis, onset of labor, and EBF initiation within one hour were the independent predictors of mortality among neonates admitted with neonatal sepsis.